Investigating the iso principle: the effect of musical tempo manipulation on arousal shift - Goldschmidt, Daniel, author; Knight, Andrew, advisor; LaGasse, A. Blythe, committee member; Graham, James, committee member (Colorado State University. Libraries, 2020)
The iso principle is a well-known concept in music therapy practice wherein a clinician meets a client at a current body state with a musical element, then moves them to a new body state by modulating the musical element. However, few scholars agree on what bodily states and musical elements define the iso principle, which limits music therapy clinicians' targeted application of the concept. Further, it appears there have been no studies objectively addressing physiologic change during the iso principle. The purpose of this study was to investigate arousal shift during iso principle-informed tempo change in a musical stimulus. Arousal was measured via physiological responses (galvanic skin response [GSR]) and self-perception (self-assessment manikin [SAM]). Participants' (n = 9) took part in a randomized block design with control in which they completed a mindfulness-based intervention before listening to one of three five-minute auditory stimuli: 1) an iso principle-informed song, 2) a compensation principle-informed song, and 3) a spoken short story. GSR data from participants did not show statistically significant differences between the iso principle and compensation principle, but did show significant differences between musical conditions and speech. While the music was designed to increase arousal using the iso principle, overall there was a reduction in arousal levels over the experimental period. Participants' self-ratings of their arousal shifts (SAM scores of arousal) showed a perceived increase in arousal during all conditions. Limitations, clinical implications, and future directions are discussed.
Keywords: iso principle; galvanic skin response; music therapy